Perencanaan Arsitektur Enterprise Untuk Penerapan Standar Nasional Pendidikan (SNP) Menggunakan TOGAF ADM 9.2 di SMP Unggul Sakti Kota Jambi - Morgan, Antonio; Zaenal Abidin, Dodo (LPPM Universitas Dinamika Bangsa, 2023)
We can now feel the use of technology in services in various sectors, one sector that is quite influential in human life which cannot be separated from the use of technology, namely in the education sector. Education is a stage where students are guided and directed to get quality education in accordance with the National Education Standards. Implementation and fulfillment of National Education Standards can be done from various perspectives, one of which is from a technological perspective. Currently, SMP Unggul Sakti Jambi does not yet have an integrated information system in carrying out academic operations, therefore an enterprise architecture design is needed to develop and build information systems and information technology at schools. Enterprise architecture has the meaning of defining, classifying, planning and designing the connectivity of the various components that make up an enterprise. This study uses the TOGAF ADM framework which is limited to the initialization, vision architecture, business architecture, information system architecture, and technology architecture stages. The result of this research is a blueprint for an integrated information system architecture design that can be used by schools to support the implementation of the National Education Standards in carrying out business processes.